2022
DOI: 10.3389/fphar.2022.823944
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Hospital Pharmacists in Central China Towards Adverse Drug Reaction Reporting: A Multicenter Cross‐Sectional Study

Abstract: Background: Healthcare professionals’ knowledge and attitudes towards adverse drug reactions (ADRs) and ADR reporting play a significant role in pharmacovigilance. This study aims to investigate the gap between knowledge and practice in ADR reporting among hospital pharmacists.Methods: This study is a multi-center, cross-sectional study based on a questionnaire survey. A semi-structured questionnaire was developed including knowledge, attitudes, and practices (KAP) towards ADR reporting. From October to Novemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…Attitude is a driving force behind ADR reporting, and thus a positive attitude can encourage timely ADR reporting. 52,64 Our study found that participants aged 40 or younger were more negative toward ADR reporting compared to those over 40 years old (P = .008). This could be due to older healthcare workers having more experience with ADR cases, and thus a better understanding of the harm ADRs can cause to patients, in addition to having undertaken more training in ADR than their younger counterparts.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Attitude is a driving force behind ADR reporting, and thus a positive attitude can encourage timely ADR reporting. 52,64 Our study found that participants aged 40 or younger were more negative toward ADR reporting compared to those over 40 years old (P = .008). This could be due to older healthcare workers having more experience with ADR cases, and thus a better understanding of the harm ADRs can cause to patients, in addition to having undertaken more training in ADR than their younger counterparts.…”
Section: Discussionmentioning
confidence: 63%
“…This could be due to older healthcare workers having more experience with ADR cases, and thus a better understanding of the harm ADRs can cause to patients, in addition to having undertaken more training in ADR than their younger counterparts. 52 Additionally, pharmacists were more negative toward ADR reporting than were doctors ( P = .002) or nurses ( P = .008). 47 It has been reported that many pharmacists feel that ADR reporting adds to their workload and is time-consuming.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frontiers in Pharmacology frontiersin.org coping strategies (Zhang et al, 2020). The difference of knowledge level has great significance on HCPs' practice level, which indicates education intervention is one strategy for better practice (Gidey et al, 2020;Hu et al, 2022). Certain attitudes of HCPs also have a great impact on behavior: HCPs who agree that NCDP policy can reduce the burden of chronic disease patients and alleviate the contradiction between doctors and patients have higher degree of satisfaction to the policy and are more inclined to have better practice.…”
Section: Discussionmentioning
confidence: 99%